Temporal and Spatial Characteristics of Cataract Surgery Rates in China - Wu X; Shi X; Li H; Guo Z (Dove Medical Press, 2021)
Xiaoming Wu, 1, 2 Xiujing Shi, 1, 2 Honglei Li, 1, 2 Zhen Guo 1, 2 1Qingdao Eye Hospital of Shandong First Medical University, Qingdao, People’s Republic of China; 2State Key Laboratory Cultivation Base, Shandong Provincial Key Laboratory of Ophthalmology, Shandong Eye Institute, Shandong First Medical University & Shandong Academy of Medical Sciences, Qingdao, People’s Republic of ChinaCorrespondence: Zhen GuoState Key Laboratory Cultivation Base, Shandong Provincial Key Laboratory of Ophthalmology, Shandong Eye Institute, Shandong First Medical University & Shandong Academy of Medical Sciences, 5 Yanerdao Road, Qingdao, 26600, People’s Republic of ChinaEmail guoz@sdfmu.edu.cnObjective: The aim of the current study was to explore the spatial and temporal distribution characteristics of registered cases of cataract surgery in China from 2013 to 2017.Methods: A database for spatial analysis of cataract surgery in China in 2013– 2017 was established using ArcGIS10.0 software as a platform for data management and presentation. Spatial autocorrelation analysis of cataract surgery was undertaken, and temporal and spatial scan analysis was done using SaTScan 9.5 software.Results: From 2013 to 2017, annual cataract surgery rates (CSRs) in China were 1200, 1400, 1782, 2070, and 2205 per 1 million population, indicating a gradually increasing trend. Local Moran’s I autocorrelation analysis showed that there was spatial clustering of CSR in China, with Anhui being a low-high clustering region. Findings of global hotspot analysis Getis-Ord General G showed that General G index of national CSR was < 0.01, Z = 1.12, P = 0.26. Findings of staged spatial-temporal scan analysis indicated that 18 areas of aggregation were found in 2 stages. Observed differences in each clustering area were statistically significant (P < 0.05).Conclusion: CSRs in China showed increasing trend year by year and were randomly distributed, with spatial clustering, and Anhui was reported as a low-high clustering region. However, high-risk areas still persist, requiring focused attention and targeted prevention and control measures.Keywords: cataract surgery, geographic information system, spatial autocorrelation analysis, spatiotemporal analysis